Infringement of Rights of Children in Conflict With the Law. A Case Study in Lira District. - Francis Aryam (Uganda Christian University, 2024)
This Study was about the infringements of rights of children in conflict with the law in Uganda. This study sought to examine the effectiveness of the existing laws and institutional framework relating to rights of children and challenges faced by these institutions in Uganda. Through doctrinal research methodology, the study specifically examines the existing laws of children in conflict with the law in Uganda and applicability in civil sector in Uganda. The research focuses on the circumstances which give rise to children in conflict with the law in Uganda and legalities taken into account while resolving the custody, care and control of children as supported by the law. It also discusses the problems experienced in dealing with law in regards to the study. It provides possible interventions to streamline cases of custody of children. The proposed research took the form of a new research but on an existing research subject. In order to satisfy the objectives of the dissertation a qualitative research was held. The research findings of the study reveal a number of factors capable of stalling the proper regulation of children in conflict with the law in Uganda, in the view of this findings, the study recommends proper implications of existing laws, improvements in monitoring and assessments of juvenile delinquency in Uganda among other things.